KONSTRUKSI IDENTITAS GURU PROFESIONAL SEBAGAI KOMUNIKATOR PENDIDIKAN: STUDI FENOMENOLOGI IDENTITAS GURU PROFESIONAL PADA KOMUNIKASI PENDIDIKAN DI KOTA BANDUNG - Jenny Ratna Suminar (Indonesian Journal of Dialectics, 2011)
This study aimed to elaborate how teachers identified themselves within the context of professionalism. This study used qualitative method with phenomenological approach to answer some research questions as follow: how did they construct the meaning of teaching as a profession, how did they construct the teacher professionalism identities, and what were communication competencies of professional teachers as education communicators. Data were collected from 13 teachers selected purposively as key informants.The results indicated two categories of teacher’s meaning identity i.e. teachers as noble profession (positive) and teachers as marginal profession (negative). Teachers perceived positive meaning as such that teaching was an inspiring profession, social profession, and civilization transforming profession to build nation characters. Meanwhile, teachers perceived negative meaning as such that teaching was merely reserved profession and/or marginal profession.Other findings suggested that these personal characteristics were mostly embedded in female teachers who had motherly instincts to nurture and educate. Teacher professionalism was defined as a label for teachers who possessed qualifications, such as having vision and mission in education, strong character and integrity, graduated from college of education, entertaining, ethical and fully competent. Teacher certification was perceived from positive perspective as a proof of professionalism and as a requirement for improving teachers welfare. Research findings might be able to be adapted by policy makers in improving the recruitment system. Better teachers and educational college managers or administrators could be recruited to generate better education communicators that might provide leverage to continuously improving the quality of human resources in Indonesia.